2006
DOI: 10.1080/07421656.2006.10129329
|View full text |Cite
|
Sign up to set email alerts
|

Technology Training for Future Art Therapists: Is There a Need?

Abstract: The focus of this study was art therapy students' and professionals' perceptions of their preparedness to understand and deal with technology as an art media and work tool within the practice of art therapy. To study the need for training in technology, surveys were sent to 177 current art therapy students and practicing art therapists resulting in a 32.2% return rate. The survey targeted American Art Therapy Association (AATA) members who were either current students or practicing art therapists. Credentialed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…The importance of suitable specialist training in the use of digital technology for art therapists providing therapy online has been highlighted in previous research studies (Carlton, 2014;Collie et al, 2006;Orr, 2006Orr, , 2012 and echoed in survey responses we gathered. In case of the recent accelerated move to online art therapy provision, limited training and access to suitable therapy space as well as limited support in needing to make significant adaptations to practice had implications for therapists' confidence, which was found to be generally lower in providing online art therapy sessions in relation to face to face.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The importance of suitable specialist training in the use of digital technology for art therapists providing therapy online has been highlighted in previous research studies (Carlton, 2014;Collie et al, 2006;Orr, 2006Orr, , 2012 and echoed in survey responses we gathered. In case of the recent accelerated move to online art therapy provision, limited training and access to suitable therapy space as well as limited support in needing to make significant adaptations to practice had implications for therapists' confidence, which was found to be generally lower in providing online art therapy sessions in relation to face to face.…”
Section: Discussionmentioning
confidence: 70%
“…Limited research to date examined art therapists' attitudes to digital technology and its use in art therapy sessions with clients, but has not yet given insights into the client perspective. Several surveys among US-based art therapists over the last two decades were in fact concerned primarily with digital technology use and ownership and less with the actual practice with clients (Orr, 2006(Orr, , 2012Peterson, 2010;Peterson et al, 2005). Some key messages coming from these investigations included art therapists' willingness to adopt new digital media for therapy only once their benefits for clients and any risks are known.…”
Section: Introductionmentioning
confidence: 99%
“…Four articles from two US-based research teams focused entirely on the views and opinions of art therapists on the use of digital technology in art therapy practice and utilized a survey design ( Table 2 : Peterson et al, 2005 ; Orr, 2006 , 2012 ; Peterson, 2010 ). They gathered both the therapists’ experience (based on practice) and expectations (based on personal attitudes).…”
Section: Resultsmentioning
confidence: 99%
“…Across the studies, a trend emerged suggesting an increasing use of digital technology within art therapy sessions. A study comparing results from surveys undertaken 7 years apart, found that between 2004 and 2011 art therapists increased their use of digital media in their art therapy practice with clients: from 19 to 32% using technology as an artmaking tool during sessions and from 2.4 to 9.4% using web camera communication during sessions ( Orr, 2006 , 2012 ). In addition, in the 2011 survey, 11.8% respondents reported using online chat ( Orr, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several articles and survey studies suggest that art therapists were initially cautious about welcoming technological media into the art therapy studio (Peterson et al, 2005;Asawa, 2009;Peterson, 2010), with concerns regarding the loss of tactile and sensual qualities in digital art making environments (McNiff, 1999). Nevertheless, the need for technology training for art therapy students was acknowledged by students (Orr, 2006), and views on virtual technologies have been changing, highlighting the importance of "broadening definitions of art materials and contexts" (Kapitan, 2007, p. 51). In the current climate of COVID-19, the use of technology in art therapy has been recognized, drawing attention also to ethical and safety concerns in the operation of these media (Alders et al, 2011).…”
Section: Digital Artmaking and Vr In Art Therapymentioning
confidence: 99%